Revealing the truth: Catalonia the self-sacrificial victim of Spain - León-Solís, Fernando (Ámbitos. Revista Internacional de Comunicación, 2019)
This article offers a analysis on the narrative strategies used by Josep Antoni Duran i Lleida, the leader of the center-right catalanist coalition Convergència i Unió, in his speech in defence of the new Statute of Autonomy of Catalonia presented in the Spanish Parliament in 2005. The article suggests that Duran’s speech followed a long-standing grand narrative frame organized around the following three interrelated features: a) an absolute notion of historico-political ‘truth’ and ‘reality’ that the Catalan (as opposed to Spanish) political classes are in possession of; b) the double role of Catalonia as victim and redeemer of Spain; and c) the construction of the Statute debate as a turning point in the history of Spain, as the moment for the potential redemption of Spain with the help of Catalonia. The article argues that this particular narrative framework, which ultimately precludes the idea of total separation, is a manifestation of the dual position of Catalonia within Spain as a region with a strong sense of identity but also with strong economic and political interests within Spain.